Conference Interpreting: Quality in the Ears of the User - Kurz, Ingrid (Meta)

(untitled) (Les Presses de l'Université de Montréal, 2001)
AbstractWhat do the recipients of interpretation mean by “good interpretation”? What are the features they consider most important and what do they find irritating? Following a brief overview of user expectation surveys, the paper contends that the target audience is an essential variable in the interpretation equation. Quality of interpretation services is evaluated by users in terms of what they actually receive in relation to what they expected. Consequently, measurements of service quality that do not include user expectations miss the point.